1967
DOI: 10.1161/01.res.20.2.162
|View full text |Cite
|
Sign up to set email alerts
|

Vascular and Extravascular Volumes of the Kidney of Man

Abstract: Indicator dilution techniques were used to determine the vascular and extravascular volumes of the normal human kidney. Renal volumes were corrected to 1.73 m 2 and refer to one kidney. The renal blood volume (V I0 ) averaged 34.8 ±3.1 ml; the water contained in the distribution volume of labeled inulin (Vi X ") averaged 48.8 ± 9.0 ml, and that of tritiated water ) were derived and averaged 27.4 ± 6.2 ml and 93.7 ± 14.3 ml, respectively.Correction for recirculation by exponential extrapolation was studied and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

1969
1969
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 20 publications
2
16
0
Order By: Relevance
“…Despite the geometrical simplifications involved in this method it is probable that it yields a volume which closely approximates that of the kidney itself, the main renal vessels and the small amount of adjacent tissues supplied by the renal artery. This is supported by the results from the normal subjects in whom the mean was 215 ml, and thus only slightly above the value of 180 ml estimated as the in vivo volume of the human kidney by Effros, Lowenstein, Baldwin, and Chinard (25).…”
Section: Introductionsupporting
confidence: 64%
See 3 more Smart Citations
“…Despite the geometrical simplifications involved in this method it is probable that it yields a volume which closely approximates that of the kidney itself, the main renal vessels and the small amount of adjacent tissues supplied by the renal artery. This is supported by the results from the normal subjects in whom the mean was 215 ml, and thus only slightly above the value of 180 ml estimated as the in vivo volume of the human kidney by Effros, Lowenstein, Baldwin, and Chinard (25).…”
Section: Introductionsupporting
confidence: 64%
“…DIS CUSSION The reliability of the indicator-dilution technique for the measurements of total RBF and renal transit time "has been discussed in detail elsewhere (12,(23)(24)(25)29). In the present study, since relatively high RBF's were -found in some patients with acute anuria, it would seem relevant to consider whether this was the result of an overestimation due to errors of the dye-dilution method.…”
Section: Resultsmentioning
confidence: 72%
See 2 more Smart Citations
“…A volume of 0.9 ml absolute ethanol was added to 0.1 ml of blood, and the mixture in the tube was mixed and centrifuged. A volume of 0.2 ml of the alcohol supernatant was added to 10 ml of a dioxane scintillation mixture described earlier (24), and carbon-14 and tritium counts were obtained in a liquid scintillation spectrometer. Quinine determinations were made fluorometrically: A 0.5 ml volume of the alcohol supernatant was added to 5.0 ml of water and 0.5 ml of 1 N H2SO4.…”
Section: Methodsmentioning
confidence: 99%